FEATURES OF THE APPLICATION OF THE THEORY OF INVENTIVE PROBLEM SOLVING IN CREATIVE TECHNOLOGY IN HIGHER EDUCATION - Onarkulov, K.; Yakubova, Sh.; Yusupova, F. (SCIENCE and SOCIETY, 2022)
The article considers the main theoretical provisions of the theory of inventive problem solving, which is the statement that technical systems develop according to objective, cognizable laws, which are revealed by studying large amounts of scientific and technical information and the history of technology, non-standard tasks are considered as creative tasks, with partially algorithmic solution.